Status Epilepticus due to Intraperitoneal Injection of Vehicle Containing Propylene Glycol in Sprague Dawley Rats - Evon S. Ereifej; Seth M. Meade; Cara S. Smith; Keying Chen; Nanette Kleinman; Jeffrey R. Capadona (Veterinary Medicine International)
Published reports of status epilepticus due to intraperitoneal injection containing propylene glycol in rats are sparse. In fact, there are no reports specifying a maximum safe dose of propylene glycol through intraperitoneal administration. We report here a case of unexpected seizures in Sprague Dawley rats after receiving an intraperitoneal injection containing propylene glycol. Nine-week-old, 225–250 gram male rats were reported to experience tremor progressing to seizures within minutes after given injections of resveratrol (30 mg/kg) dissolved in a 40 : 60 propylene glycol/corn oil vehicle solution by direct intraperitoneal (IP) slow bolus injection or via a preplaced intraperitoneal catheter. The World Health Organization suggests a maximum dose of 25 mg/kg/day of propylene glycol taken orally and no more than 25 mg/dL in blood serum, whereas the animals used in our study got a calculated maximum 0.52 g/kg (25 times lower dose). Blood tests from the seizing rat support a diagnosis of hemolysis and lactic acidosis which may have led to the seizures, all of which appeared to be a consequence of the propylene glycol administration. These findings are consistent with oral and intravenous administration of propylene glycol toxicity as previously reported in other species, including humans. To our knowledge, this report represents the first published case of status epilepticus due to an IP injection containing propylene glycol.